2001
DOI: 10.2166/wst.2001.0553
|View full text |Cite
|
Sign up to set email alerts
|

Biofilters - the influence of different filter materials and different operating conditions on the reduction efficiency

Abstract: A series of biofilter materials were tested for performance efficiency in treating ventilation air from pig sheds. Two different phases were conducted. In phase A five different biofilter materials were tested with the aim of selecting the best material regarding the odor reduction and over all efficiency. In conclusion of phase A, biochips, a new filter material, was selected due to its high average odor reduction (81%) in combination with a very low flow resistance (less than 30 Pa for filter volume loads of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Reduction in odour nuisance plays an important role for strategies concerning where to permit pig production facilities to be located and determines the maximum size of the facilities. So far, strategies to reduce odour mainly focused on technical approaches such as bio-filters (Hartung et al, 2001;Sheridan et al, 2002) and bio-scrubbers (Hahne et al, 2003). In addition, studies have been made to limit microbial activities in manure or to mask odour with other odourous compounds (Stevens et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in odour nuisance plays an important role for strategies concerning where to permit pig production facilities to be located and determines the maximum size of the facilities. So far, strategies to reduce odour mainly focused on technical approaches such as bio-filters (Hartung et al, 2001;Sheridan et al, 2002) and bio-scrubbers (Hahne et al, 2003). In addition, studies have been made to limit microbial activities in manure or to mask odour with other odourous compounds (Stevens et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia REs increased as the MC of the medium increased from 20% to 50%. Odor REs were affected to a greater extent by the inlet odor concentration while NH 3 REs were affected to a greater extent by the τ (Hartung et al, 2001). Nicolai and Janni (1997) 4.4 78% 86% 50% Hartung et al 2001 Biofilter 1 (old medium) 6 88% -15%…”
Section: Pilot-scale Biofiltersmentioning
confidence: 93%
“…Hardwood woodchip medium was used for the biofilter bed that had an EBRT of 3.25 s. The biofilter was able to reduce odor and NH 3 concentrations by 62 and 73%, respectively, and reduced overall emissions from the barn by 58 and 37%, respectively. Hartung et al (2001) examined two parallel biofilters treating emissions from a piggery in Germany. These biofilters' media were of coconut and peat fiber mixture and 6.5 years old.…”
Section: Pilot-scale Biofiltersmentioning
confidence: 99%
See 1 more Smart Citation
“…In such studies biofilters have been shown to reduce the emissions of odors and volatile compounds up to 90 percent reduction efficiency 169,170 . evaluated several types of filter media for biofilters for odor reduction and found that biochips and coconut peat had a reduction of odor emissions of eighty one percent and wood bark odor reduction of sixty two percent 171 Determine the viable airborne MRSA concentration and particle size both bacterium which has developed resistance to currently available beta-lactams and cephalosporin and has emerged as a pathogen of great public health concern 1,11,31,[173][174][175] .…”
Section: Biofiltersmentioning
confidence: 99%